Development of a Social Media–Based Digital Da’wah Training Model for Enhancing Teachers’ Professional Development - Muhammad Subchan Munawwar; Dina Nur Wulan; M. Djamal (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The rapid expansion of social media has significantly transformed the landscape of da’wah and educational practices, requiring teachers to develop professional competencies that are responsive to digital environments. Despite this shift, systematic training models that integrate digital da’wah with teacher professional development remain limited. This study aims to examine and formulate a conceptual model of social media–based digital da’wah training to support the professional development of teachers. The research employs a qualitative approach using a literature study design (library research). Data were collected from relevant academic sources, including peer-reviewed journals, scholarly books, and authoritative documents related to digital da’wah, media literacy, and teacher professional development. Data analysis was conducted through content analysis to identify key themes, conceptual patterns, and theoretical linkages across the literature. The findings indicate that an effective digital da’wah training model for teachers encompasses several core components: digital literacy, da’wah content creation skills, audience engagement strategies, integration of digital da’wah into pedagogical practices, and ethical awareness in the use of social media. Furthermore, the training model should be structured in a gradual and sustainable manner and supported by institutional policies and a conducive organizational culture. This study contributes to the theoretical discourse on digital da’wah by offering a structured conceptual framework that can serve as a reference for developing contextually relevant teacher training programs in the digital era.